2019
DOI: 10.3390/urbansci3040111
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Devices with Multifunctional Sound Level Measurement Applications: Some Experiences for Urban Acoustics Education in Primary and Secondary Schools

Abstract: Geo-referenced sound data are often used in the field of acoustics education to learn about the urban acoustic environment. Simple soundwalks and sound collections are also employed, in which acquiring additional information such as visual data, recorded sound data, and GPS location data are helpful to produce a map with sound data and sound collection and to carry out more profound discussions in educational activities. In order to enrich these acoustic educational and environmental survey activities with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The technical information of the NoiseCapture app is available on its web site [9] and documented in [10]. Before the measurements, the app and the device were calibrated using a standardised sound level meter (SLM) (Class 1), and its validity, confirmed via the method in [11,12], was reported in [8]. The results of a sound map made via soundwalk with this app give the noise level range (dBA, L Aeq ) along the soundwalk course.…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical information of the NoiseCapture app is available on its web site [9] and documented in [10]. Before the measurements, the app and the device were calibrated using a standardised sound level meter (SLM) (Class 1), and its validity, confirmed via the method in [11,12], was reported in [8]. The results of a sound map made via soundwalk with this app give the noise level range (dBA, L Aeq ) along the soundwalk course.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…It was calibrated and checked for accuracy using a Class 1 sound level meter (SLM). For details of the accuracy check results, see [8], and for the method used for the accuracy check, see [11,12]. The overall noise level and characteristics of the surveyed area and how these changed after the declaration of the state of emergency was lifted were investigated by way of a soundwalk using NoiseCapture.…”
Section: Additional Information From the Soundwalk Surveymentioning
confidence: 99%
“…Thus, a possible effect can be observed and interpreted as the increased traffic volume observed and construction works in this area in May 2020: During the state of emergency, a certain number of people used a car or motorbike for commuting, shopping, and travelling for various purposes, which should have increased traffic volume in this area. For reference, previous survey in the same area (except for the point 6) in August-October 2019 [11] showed that: Instantaneous noise levels (dBA, slow, peak) were 44.8 dBA (minimum, Point 1) to 64.8 dBA (maximum, Point 5). This range roughly corresponds to the above results, which can be inferred that, though the variation due to the day is observed in Table 1, the noise levels fall into the range observed in those observed in usual state.…”
Section: Surveyed Area and Methodsmentioning
confidence: 94%
“…This area is occupied by mainly two-storey detached houses, but there is also a somewhat large number of small and large apartments of three to five storeys. In 2019, the noise levels of this area were surveyed as a follow-up to the author's previous study [11], and the results demonstrated that it was rather quiet except for occasional cars passing by. For other data sets in the same area, three sets of geo-referenced sound data taken in August-October 2019 using iPhone XS and three apps (dB Meter Pro, Decibel X and SoundLog) are available in reference [11] in which instantaneous SPL (dBA, slow, peak) taken by dB Meter Pro and Decibel X and LAeq taken by SoundLog.…”
Section: Surveyed Area and Methodsmentioning
confidence: 97%
See 1 more Smart Citation